How do Teachers Overcome Failed Interaction After Asking Question? - Rahman, Mahda Haidar; Subyantoro, Subyantoro; Yuniawan, Tommi; Pristiwati, Rahayu (Proceedings of International Conference on Science, Education, and Technology, 2024)
Interaction between teachers and students is important in learning. Interaction often begins with a question from the teacher to the students, even if it is just a rhetorical question (a question that does not require an answer). Although questions start an interaction, it is not uncommon for questions to be the cause of interaction failure. Questions that do not get a good response from students can result in the failure of classroom interaction. In fact, there are many functions of questions, not only to measure students' understanding, but also to stimulate critical thinking and active involvement in learning. Based on this, it is important to learn how teachers deal with questions that do not get a response from students so that there is no failure of interaction. The purpose of this study is to find out how teachers overcome interaction obstacles if the questions given do not get a response from students. This study is qualitative research that uses classroom discourse analysis method. Data were collected from two language classes from different schools. What teachers do to overcome interaction failure in learning is repeating questions, paraphrasing question sentences, and giving additional questions or accompanying questions. This method is a way that is often used by teachers.